Web-based course registration system using bluetooth technology - Mohamad Hazriman, Bin Husein (Universiti Malaysia Sarawak, UNIMAS, 2006)
This web-based system is designed to facilitate Universiti Malaysia Sarawak student for registering their courses according to the current semester by using Bluetooth technology. Besides, the purpose of this project is to enhance the security level towards the system in Bluetooth technology. The research made shows that the Bluetooth technology still lacks of security measures. Thus, one security mechanisms is required to protect the system. That security is Secure Socket Layer (SSL). SSL can secure the data travel wirelessly. This webbased system will implement the SSL as a solution to solve the current weaknesses of Bluetooth technology. Besides providing the registration facilitation, this project can give significant to people outside. The development of this project will become a basic prototype to expand the Bluetooth technology widely and to improve the security level.